2001
DOI: 10.1002/1521-4095(200109)13:18<1389::aid-adma1389>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Mediated Growth Approach for Shape-Controlled Synthesis of Spheroidal and Rod-like Gold Nanoparticles Using a Surfactant Template

Abstract: A seed‐mediated growth approach to improved monodispersity of nanoparticles that involves controlling nucleation and growth in solution is presented. Using this approach, spheroidal and rod‐like gold particles (see Figure) could be prepared in the presence of a rod‐like micellar template. The aspect ratio of the particles could be varied from 1 to 10 by varying the ratio of preformed seed to metal salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,416
2
17

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,665 publications
(1,489 citation statements)
references
References 10 publications
28
1,416
2
17
Order By: Relevance
“…The absorption spectrum is sensitive to various factors such as particle size [1−3] and shape [4,5], particle charge [6−10], aggregation state [11,12], and physicochemical micro-environment of the surrounding medium [13−16]. The increase of the electron density on the particle results in the increase of the plasma frequency of the electrons in the particle, leading to a blue shift of the plasmon absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectrum is sensitive to various factors such as particle size [1−3] and shape [4,5], particle charge [6−10], aggregation state [11,12], and physicochemical micro-environment of the surrounding medium [13−16]. The increase of the electron density on the particle results in the increase of the plasma frequency of the electrons in the particle, leading to a blue shift of the plasmon absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…That was the first preparation of uniform gold nanorods using a "soft template." Jana et al [15][16][17] similarly reported seed-mediated gold nanorod synthesis using a suitable reaction solution. The seed particles were prepared in a CTAB solution using NaBH 4 as a reducing agent.…”
Section: Preparation Of Gold Nanorods and Their Optical Propertiesmentioning
confidence: 99%
“…In this paper it is shown that different sized nanoparticles can be prepared by varying the seed concentration. Other seeded growth methods have already been reported both for gold and silver nanoparticles [10,[23][24][25][26] but not with HQ as a reducing agent. HQ is widely used in photographic film development and selectively reduces silver ions in the presence of metallic silver nanoclusters [10,27,28].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%